Efektivitas Penggunaan Aplikasi Bima terhadap Pengelolaan Stok Opname B21 Digital Printing - Elvanda Sahra Shabrina; Fani Khoirotunnisa (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
The purpose of this study was to determine the effectiveness of using the bima application on stock management of opname b21 digital printing. Digital-based systems have changed the way of working in the printing world by speeding up processes and increasing efficiency. This research uses a qualitative approach that aims to understand the phenomena experienced by research subjects, such as behavior, perceptions, motivations, and actions. This application is effectively integrated in the company's operational activities. The "Material Stock" feature enables fast and accurate stock counts, reducing reliance on error-prone manual recording. The stock-taking process becomes more efficient, increasing team productivity. In addition, the BIMA app supports various other activities, such as raw material procurement and sales monitoring. Managers can access sales reports directly, allowing them to make faster decisions regarding procurement. Data integration between sales and stock allows for better planning of inventory requirements, reducing the risk of stock-outs or overstocks. Overall, the BIMA app provides significant benefits in efficiency and stock management, streamlining business processes, and improving B21 Digital Printing's performance and competitiveness in the market. The features help customer service and managers make informed decisions and be responsive to changes in demand, which in turn contributes to customer satisfaction.